AGAMA, KEPERCAYAAN, DAN KELESTARIAN LINGKUNGAN STUDI TERHADAP GAYA HIDUP ORANG RIMBA MENJAGA LINGKUNGAN DI TAMAN NASIONAL BUKIT DUA BELAS (TNBD)-JAMBI - Saleh, Syamsudhuha (Sekolah Pascasarjana UGM, 2014)
This article tell about the role of belief systems in maintaining forest jungle. People who lived in the jungleis a group of tribes living in the jungle. Theirâs lifestyle nomadic that is moved from one forest otherforest sticks. Forests for the jungle serves as a residence. Forests for them not only as a home but ratherserves as a source of life. If the forests are threatened, it also threatened the life of the jungle. But latelywhere the jungle has been threatened by environment pollution and looting forest. The government hasbeen unreliable in forest preservation and the existence of the jungle. When the government can notbecame a good protector, that makes the people who lived in the jungle are trying for them selves inmaintaining a source of life. With a belief system adopted, the jungle since centuries has been keepingthe forest. With the embraced the belief system of the jungle is able to preserve the environment